A Comparison of Cancer Incidence among Physician Specialists and the General Population: A Taiwanese Cohort Study. Issue 3 (4th October 2013) - Lin, Shih‐Yi; Lin, Cheng‐Li; Hsu, Wu‐Huei; Wang, I‐Kuan; Chang, Chiz‐Chung; Huang, Chiu‐Ching; Kao, Chia‐Hung; Liu, Shu‐Hui; Sung, Fung‐Chang
Abstract : A Comparison of Cancer Incidence among Physician Specialists and the General Population: A Taiwanese Cohort Study: Shih‐Yi LIN, et al . Graduate Institute of Clinical Medical Science, College of Medicine, China Medical University, Taiwan — Background: Physicians are frequently studied as a population that experiences extremely high stress, burnout, and prolonged working hours that might harm one's health. However, they have sound medical knowledge and have easy access to medical resources. We studied the incidence of cancer among Taiwanese physicians using a nationwide cohort study design. Methods: Data were obtained from the National Health Insurance (NHI) system in Taiwan. The physician cohort contained 22, 309 physicians, and each physician was randomly frequency‐matched according to age and sex with 4 people from the general population. Results: The overall incidence ratio of cancer was 27% lower in the physician cohort than in the nonphysician comparison cohort (33.9 vs. 46.5 people per 10, 000 person‐years, crude hazard ratio (HR)=0.73, 95% CI=0.70, 0.76). The adjusted HR was 0.78 (95% CI=0.72, 0.84). Female physicians experienced a higher incidence rate ratio of overall cancer, compared to male physicians (crude HR=1.17, 95% CI=1.03, 1.33 vs. crude HR=0.70, 95% CI=0.67, 0.74, respectively). Physicians were at a significantly higher risk of thyroid cancer (HR 1.75, 95% CI=1.14, 2.68), prostate cancer (HR=1.54, 95% CI=1.21, 1.97), breast cancer (HR=1.45, 95% CI=1.00, 2.09), and non‐cervical gynecological cancer (HR=4.03, 95% CI=1.77, 9.17), compared with the general population. Conclusions: Physicians are at lower overall risk of cancer than the general population, apart from cancer of the thyroid, prostate, breast, and non‐cervical gynecological cancer.